Plasma Dynamics and Pulse Shape Rules in Laser Heating of Opaque Targets in Ai - Habib, Bassam Hanna (Iraqi Journal of Physics, 2010)
A theoretical model is developed to determine time evolution of temperature at the surface of an opaque target placed in air for cases characterized by the formation of laser supported absorption waves (LSAW) plasmas. The model takes into account both plasma dynamics and time variation of incident laser pulse (i.e. pulse shape or profile).Shock tube relations were employed in formulating plasma dynamics over target surface. Gaussian function was chosen in formulating the pulse profile in the present modeling